The effect of customer value and trust on customer satisfaction and its impact on customer loyalty (Survey of Heavy Equipment Excavator Spare Parts Consumers at CV. Bandung Jaya Diesel, Bandung City) - Yudhi Koesworodjati; Ratu Hedy Syahidah Budiarti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The purpose of this study is to determine the Influence of Customer Value and Trust on Customer Satisfaction and its impact on Costumer Loyalty Survey on Costumer Spare Parts Excavator in CV. Bandung Jaya Diesel Bandung. This research was conducted by taking a sample of 70 people. Analysis of the results of this study using path analysis. The results of his research as follows: The value of the Subscriber that directly determines the change in customer satisfaction is 27% then through the relationship with the trust of 15%, the total Customer Value determines the changes - the change in customer satisfaction by 42%. In total, 39% of Customer Satisfaction changes are the effect of Confidence with 24% details is a direct influence, then 15% through its relationship with Customer Value. Customer value and Trust together affect Customer Satisfaction by 81%. The amount of influence is proportionally caused by other variables beyond Customer Value and Trust that is equal to 19%. The influence of the variable (Y) Customer Satisfaction on Costumer Loyalty with regression coefficient of 0.867 with other factors other than variable (Z) Costumer Loyalty of 0.133 Thus it can be concluded that there is influence Customer satisfaction (Y) to Costumer loyalty (Z) of 86.7 % and other factors affecting Costumer loyalty besides customer satisfaction (Y) 13,3% for promotion, price, etc